THE ACCOUNTANT'S FUNCTION IN DETERMINATION OF NET INCOME. - Bomeli, Edwin C. (The Accounting Review, 1961)
Abstract Although social implications may exist, businesses are formed primarily in response to ownership conviction that profits can be obtained from operation. In order to measure operating results, to gauge the effectiveness of management and to estimate the vitality of the owners' investment, detailed knowledge of past performance is essential. Subsequent investors and creditors need to know past performance to estimate profit making potential. Accountants in public practice may well be facilitating the administration of economic activity by making themselves available for management services. Someone however, ought to be able to compute profitability for the owners and to tell them what net return for a given period of time has been enjoyed on their investment. Economists follow the principle that costs should be related to revenues on the same price level basis and that the income in one period should be compared with the income in another period on the same price-level basis. Determination of net income is certainly one of the important functions of the accountants.